Good Housekeeping Cookery Book (London Collins & Brown, 2004)
First published in 1948, the Good Housekeeping Cookery Book is firmly established as the cook's bible, and has sold millions of copies in its various editions.
Include Color Illustration,Bibliography and Index
Keywords: Cooking -- Cooking, American -- Food supply